Multi-approach cysteine detection based on supramolecular transformation induced by G-quadruplexes. Issue 33 (30th July 2019) - Yang, Dawei; Chen, Hongbo; Li, Qian; Zhang, Xiufeng; Sun, Hongxia; Tang, Yalin
Abstract : Cysteine detection based on supramolecular transformation induced by G-quadruplexes. Abstract : Development of a cysteine (Cys) detection probe is of significant importance in clinical diagnosis. Herein, a colorimetric, chiral and fluorometric multi-approach detection probe for Cys has been designed. This probe utilized G-quadruplexes as a template to regulate the supramolecular transformation of a cyanine dye and achieve label-free and highly selective detection of Cys. Its successful use in urinary Cys measurement demonstrates good promise for practical applications.